Incongruent Spatial Distribution of Taxonomic, Phylogenetic, and Functional Diversity in Neotropical Cocosoid Palms - Freitas, Cintia; Brum, Fernanda T.; Cássia-Silva, Cibele; Maracahipes, Leandro; Carlucci, Marcos B.; Collevatti, Rosane G.; Bacon, Christine D. (Frontiers in Forests and Global Change, 2021)
Biodiversity can be quantified by taxonomic, phylogenetic, and functional diversity. Current evidence points to a lack of congruence between the spatial distribution of these facets due to evolutionary and ecological constraints. A lack of congruence is especially evident between phylogenetic and taxonomic diversity since the name and number of species are an artificial, yet commonly used, way to measure biodiversity. Here we hypothesize that due to evolutionary constraints that link phylogenetic and functional diversity, areas with higher phylogenetic and functional diversity will be spatially congruent in Neotropical cocosoid palms, but neither will be congruent with areas of high taxonomic diversity. Also, we hypothesize that any congruent pattern differs between rainforests and seasonally dry forests, since these palms recently colonized and diversified in seasonally dry ecosystems. We use ecological niche modeling, a phylogenetic tree and a trait database to test the spatial congruence of the three facets of biodiversity. Taxonomic and phylogenetic diversity were negatively correlated. Phylogenetic and functional diversity were positively correlated, even though their spatial congruence was lower than expected at random. Taken together, our results suggest that studies focusing solely on large-scale patterns of taxonomic diversity are missing a wealth of information on diversification potential and ecosystem functioning.